2023
DOI: 10.3390/ma16145058
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Portland Cement on the Selected Properties of Flue Gas Desulfurization Gypsum-Based Plasters

Abstract: The introduction of the European Union’s climate change legislation and the intended use of renewable energy sources instead of fossil fuels will significantly reduce the production of flue gas desulfurization (FGD) gypsum used as the raw material for gypsum mortar plasters’ production. This has forced mortar producers to look for alternative materials, including gypsum–cement composites. This work investigated the mechanical strength and linear extension of four gypsum–cement mortars with the gypsum content r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…The increase in mechanical strength that occurs for most plasters (Figure 3) between 28 and 180 days may be attributed to the formation of ettringite, thaumasite, or a mixture of ettringite and thaumasite crystals (woodfordite). The authors' previous work described the formation of these phases in gypsum-cement plasters in conditions of increased humidity [25]. The possibility of a beneficial effect of the above stages on the mechanical strength of the tested mortars is consistent with the research results of Tesch and Middendorf [45], who showed that a small amount of formed ettringite or thaumasite did not result in deterioration of the mechanical properties and durability of gypsum-lime mortars.…”
Section: The Influence Of Cement Addition On the Mechanical Strength ...supporting
confidence: 83%
See 3 more Smart Citations
“…The increase in mechanical strength that occurs for most plasters (Figure 3) between 28 and 180 days may be attributed to the formation of ettringite, thaumasite, or a mixture of ettringite and thaumasite crystals (woodfordite). The authors' previous work described the formation of these phases in gypsum-cement plasters in conditions of increased humidity [25]. The possibility of a beneficial effect of the above stages on the mechanical strength of the tested mortars is consistent with the research results of Tesch and Middendorf [45], who showed that a small amount of formed ettringite or thaumasite did not result in deterioration of the mechanical properties and durability of gypsum-lime mortars.…”
Section: The Influence Of Cement Addition On the Mechanical Strength ...supporting
confidence: 83%
“…The SEM image of plaster 30G/12C (Figure 11A), containing of cement, shows a higher compaction degree than the other three pla in porosity that occurs with the maturation of the plaster samples (28 ing to a more compact structure, was attributed to the increasing am products, mainly the C-S-H phase, which grow on the gypsum crys spaces between them (Figures 8B,C-11B,C). Figure 12 shows an example SEM image of the 30G/10C plaster a soning, with the characteristic structures of gypsum (G), the C-S-H thaumasite (Th) [25] marked, and the EDS spectra recorded for thes 13), confirming the presence of the phases mentioned above. XRD diffr ing the presence of thaumasite and/or mixed crystals of ettringite and 28 and 180 are provided in Figures 14 and 15.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 67%
See 2 more Smart Citations
“…The reason why FA, GBFS, SF and DG were selected as ACMs was that FA [27,28], GBFS [28], and SF [29] affect the hydration and microstructures of cementitious materials through their filling effect and pozzolanic reaction, thus effectively improving the performance of composite cementitious materials. The addition of DG [30] helps increase the number of ettringite (AFt) crystals and promote the development of strength. P•II 52.5 grade cement was purchased from China Huarun Cement Holdings Co., Ltd. (Shenzhen, China); FA, GBFS, and DG were purchased from China Baowu Environmental Science Shanxi Resource Recycling Co., Ltd. (Shanghai, China); and SF was purchased from China Aiken Silicone Co., Ltd. (Shanghai, China).…”
Section: Raw Materialsmentioning
confidence: 99%